Investigating the triple-frequency ultrasound-assisted fermented rice lees: Impact on physicochemical, structural, morphological, and metabolic properties - Mian Shamas Murtaza; Sanabil Yaqoob; Bismillah Mubeen; Aysha Sameen; Mian Anjum Murtaza; Abdur Rehman; Tawfiq Alsulami; Sameh A. Korma; Ibrahim Khalifa; Yong Kun Ma (Ultrasonics Sonochemistry)
This study examined the effect of triple-frequency ultrasound treatment (TFUT)-assisted lactic acid bacteria (LAB-L. plantarum and L. helveticus fermentation for 24-h and 48-h) on the chemical, structural, morphological, metabolic, and sensory properties of rice lees (RL). Ultrasonicated-assisted RL fermented with L. helveticus (URLH-48) had the greatest total phenolic contents (TPC) (112.1 mg GAE/m), total flavonoid contents (TFC) (163.62 mg RE/mL), and proanthocyanidin contents (PAC) (728.34 mg/mL) compared to RL (control) and other treatments. Furthermore, URLH-48 demonstrated an increase in the concentrations of quinic acid (486.96 mg/L) and gallic acid (201.42 mg/L), as determined by HPLC-UV analysis. Additionally, FTIR spectral analyses demonstrated that TFUT-assisted fermented RL exhibited a greater degree of flexibility and mobility in its secondary structures compared to RL (control). The amino acid’s profile of RL was significantly increased as LAB degraded the RL proteins, and the function of TFUT facilitates bacterial activity. Moreover, SEM observation provides convincing evidence that TFUT improves and speeds up the breakdown of proteins’ structures, resulting in irregular and dense structures. Correlation and molecular docking research suggest that TFUT has different impacts on specific RL and fermented RL characteristics. The analyses conducted using GC–MS and E-nose indicated the generation of highly volatile flavor compounds through fermentation. The sensory evaluation results show an increase in liking following fermentation and TFUT-assisted fermentation, which is attributed to the production of flavor compounds. Consequently, the combined use of TFUT-assisted fermentation markedly improves the polyphenolic composition, antioxidant capacity, flavor profile, micromorphology, and overall quality of RL, which may enhance their functionality and broaden their applications in the food industry.